IDENTIFIKASI GOLONGAN SENYAWA AKTIF ANTIMAKAN DARI DAUN TENGGULUN (Protium javanicum Burm. F.) TERHADAP LARVA Epilachna sparsa L - Agus Mandana, M. G.; Puspawati, Ni M.; Rahayu Santi, Sri (Jurnal Kimia (Journal of Chemistry); Vol. 7, No. 1 Januari 2013, 2013)
Protium is the main genusl in the family of Burseraceae which has been used traditionally as medicine, cosmetic as well as insecticide. This research aimed to isolate and identify antifeedant active compounds from leaf of Protium javanicum Burm, F which is locally known as tenggulun. Epilachna sparsa ( E.sparsa) larvae were used as bioindicator for antifeedant activity assay. The assay was performed both on crude extract, fractions, and isolate. Dried leaf powder of tenggulun (1000 g) was extracted with methanol to yield 20.89 g dark green extract. This extract showed 71.61% antifeedant activity at 0.1% (b/v). This active extract was then fractionated into n-hexane, chloroform and water fractions. The chloroform fraction was the most active which give 89.62% activity at 0.1% (b/v) compared to n -hexane (36.83%), and water fractions (1.96 %). Purification of chloroform fraction was done using silica gel column chromatography with n -hexane : chloroform (3:4) as eluent and three groups of fractions (isolates) were obtained. The most active isolate which showed 70.53% antifeedant activity at 10 ppm was found relatively pure, therefore it was then identified.  Based on phytochemical reaction, analysis of infrared spectra and ultraviolet-visible spectra, the antifeedant active isolate was identified as triterpenoid class of compounds which have functional group such as OH, CH 3 , CH 2, C=O, C=C and ? max at 245 and  416  nm.
Keywords: Protium javanicum Burm. F, tenggulun, antifeedant, triterpenoid, Epilacna sparsa